Floristic Composition, Chorotypes and Life form of the Family Caryophyllaceae, Libya: Floristic Composition, Chorotypes and Life form of the Family Caryophyllaceae, Libya (مجلة القلعة, 2025)
The aim of this research to analyze the floristic composition of the Caryophyllaceae family In Libya utilizing data from the Flora of Libya. The findings indicate that this family comprises 62 plant Sp across 18 Genes. Notably, the genus Silene is the most dominant, featuring 23 Sp, followed by Cerastium with 7 Sp. Other genes include Minuartia and Spergularia, each with 5 Sp, and Dianthus with 4 Sp.Additionally, the analysis of life forms and chorological spectra reveals a predominance of therophyte life forms, totaling 48 Sp. This is followed by chamaephytes with11 Sp. In terms of chorotypes, Mediterranean-chorotypes lead with 15 Sp followed by Mediterranean/Iranian/Turanian with 14 Sp, and Cosmopolitan regions comprising 5 Sp.Overall, this study provides valuable insights into. The diversity and distribution of the Caryophyllaceae family within the flora of Libya.
Keywords: Caryophyllaceae; - Mediterranean; – Life form; Chorotype